2008
DOI: 10.1128/mcb.00103-08
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Recognition of SUMO-Sensitive Target Genes following Modification of SF-1 (NR5A1)

Abstract: SUMO modification of nuclear receptors, including the constitutively active receptor steroidogenic factor 1 (SF-1; NR5A1), is proposed to repress their transcriptional activity. We examined the functional and structural consequences of SF-1 sumoylation at two conserved lysines (Lys119 and Lys194) that reside adjacent to the DNA-binding domain (DBD) and ligand-binding domain (LBD), respectively. Surprisingly, while previous loss-of-function studies predicted that sumoylation at Lys194 would greatly impact SF-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 59 publications
4
59
1
Order By: Relevance
“…SF-1 is SUMOylated at two conserved lysines, Lys119 and Lys194, which reside adjacent to the DBD and LBD, respectively, and this modification clearly represses SF-1 transactivation (5,22,26,67). This was attributed to the SUMOylation on Lys194, which was shown to reduce Ser203 phosphorylation, decrease coregulator binding, and cause a selective loss of binding to certain target genes (5,67). In contrast, we found that SF-1 SUMOylation was not affected by S203 phosphorylation and that SUMOylation on Lys194 is a prerequisite for SUMOylation on Lys119, which has been confirmed in other reports (22,69).…”
Section: Vol 30 2010mentioning
confidence: 99%
See 2 more Smart Citations
“…SF-1 is SUMOylated at two conserved lysines, Lys119 and Lys194, which reside adjacent to the DBD and LBD, respectively, and this modification clearly represses SF-1 transactivation (5,22,26,67). This was attributed to the SUMOylation on Lys194, which was shown to reduce Ser203 phosphorylation, decrease coregulator binding, and cause a selective loss of binding to certain target genes (5,67). In contrast, we found that SF-1 SUMOylation was not affected by S203 phosphorylation and that SUMOylation on Lys194 is a prerequisite for SUMOylation on Lys119, which has been confirmed in other reports (22,69).…”
Section: Vol 30 2010mentioning
confidence: 99%
“…We have demonstrated that ubiquitin targets SF-1 on Lys119, which is also targeted by SUMO. SF-1 is SUMOylated at two conserved lysines, Lys119 and Lys194, which reside adjacent to the DBD and LBD, respectively, and this modification clearly represses SF-1 transactivation (5,22,26,67). This was attributed to the SUMOylation on Lys194, which was shown to reduce Ser203 phosphorylation, decrease coregulator binding, and cause a selective loss of binding to certain target genes (5,67).…”
Section: Vol 30 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study identified androgen receptor interacting protein 4, a member of the Rad54 chromatin remodeling family, as a factor that interacts with sumoylated SF-1, and androgen receptor interacting protein 4 may be a cofactor that modulates SUMO-mediated fine-tuning of transcriptional repression (28). In contrast, sumoylation of SF-1 was shown to result in coordinated protein modification, such as reducing CDK7-mediated serine 203 phosphorylation (47) and reduction of DNA binding activity of SF-1 (26).…”
Section: Ubc9 and Pias1 Function As Transcriptional Coactivators Of Sf-1mentioning
confidence: 99%
“…Electrophoretic mobility shift assays (EMSA) were performed using the Light Shift Chemiluminescent EMSA Kit according to the recommendations of the manufacturer (Thermo Scientific). A 5 ′ -biotin-labelled oligonucleotide comprising an SF-1-responsive element of the mouse Amh promoter as well as mutated oligonucleotides of this motif previously described by Campbell et al [2008] were used. Twenty nanograms of 5 ′ -biotin-labelled probe were incubated with nuclear extracts of transfected HeLa cells with or without either a 200-fold excess of unlabelled target DNA or unlabelled mutated target DNA (see fig.…”
Section: Nuclear Extracts and Electrophoretic Mobility Shift Assaymentioning
confidence: 99%